Peningkatan Pemahaman Entrepreneurship Siswa-Siswi Yayasan Pondok Pesantren Depok melalui Pelatihan Business Model Canvas, Digital Marketing, dan Business Plan Proposal - Abdullah Billman; Stefanus Rumangkit; Mario Istar (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of community service activities that will be carried out is to foster an entrepreneurial spirit and increase knowledge about the business model canvas, design thinking, business plan proposal, digital marketing, and marketplace. Community Service Activities will be held at the SMK Yayasan Pondok Pesantren Depok. The target participants are students of SMK Yayasan Pondok Pesantren Depok. The problem faced by the school is the lack of training activities in schools related to entrepreneurship. The solutions offered to partners are providing training to partners on building an entrepreneurial spirit, training on digital marketing and marketplace. The method used in this PKM activity is the method of socialization / counseling, discussion, simulation, and application. The results of community service activities that have been carried out are that students of the SMK Yayasan Pondok Pesantren Depok have knowledge and are able to business model canvas, design thinking, business plan proposal, digital marketing, and marketplace.